2014
DOI: 10.1001/jama.2014.16658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High vs Low Glycemic Index of Dietary Carbohydrate on Cardiovascular Disease Risk Factors and Insulin Sensitivity

Abstract: IMPORTANCE Foods that have similar carbohydrate content can differ in the amount they raise blood glucose. The effects of this property, called the glycemic index, on risk factors for cardiovascular disease and diabetes are not well understood. OBJECTIVE To determine the effect of glycemic index and amount of total dietary carbohydrate on risk factors for cardiovascular disease and diabetes. DESIGN, SETTING, AND PARTICIPANTS Randomized crossover-controlled feeding trial conducted in research units in acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 43 publications
(77 reference statements)
7
167
1
2
Order By: Relevance
“…In another crossover study, a low-GI diet decreased insulin sensitivity and increased LDL cholesterol compared to high-GI diet in the context of high carbohydrate content, and decreased triglycerides in the context of low carbohydrate content. [39] Other than these results, none of the outcomes differed significantly between the pasta-containing low-GI diet group and the high-GI diet group. [41][42][43][44] Overall, RCTs comparing pasta to other high-GI starchy foods are lacking.…”
Section: Pasta As Part Of Low-gi Interventionsmentioning
confidence: 66%
See 1 more Smart Citation
“…In another crossover study, a low-GI diet decreased insulin sensitivity and increased LDL cholesterol compared to high-GI diet in the context of high carbohydrate content, and decreased triglycerides in the context of low carbohydrate content. [39] Other than these results, none of the outcomes differed significantly between the pasta-containing low-GI diet group and the high-GI diet group. [41][42][43][44] Overall, RCTs comparing pasta to other high-GI starchy foods are lacking.…”
Section: Pasta As Part Of Low-gi Interventionsmentioning
confidence: 66%
“…[37] Seven independent studies were included in this category with outcomes including insulin sensitivity, [38,39] HbA1c, [40][41][42] fasting plasma glucose, [38,[40][41][42][43] total plasma cholesterol, [40][41][42][43][44] low-density-lipoprotein (LDL) cholesterol, [39-41, 43, 44] high-density-lipoprotein (HDL) cholesterol, [39][40][41][42][43][44] LDL/HDL cholesterol ratio, [40,41] plasma triglycerides, [39][40][41][42][43][44] body weight, [38,[40][41][42]45] waist circumference, [40,45] and blood pressure. [39,40] We were not able to locate trials with T2D or CVD as outcome, but one study calculated the 10-year Framingham coronary heart disease (CHD) risk score. [40] • Third, 14 studies were identified where different types of pasta were compared, including 3 studies that compared whole grain to refined grain pasta, [46-48] 6 studies that compared fiber-fortified to non-fiber-fortified pasta, [49]…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent work supports the Mediterranean diet, which is relatively rich in monounsaturated fats, as a means to help to prevent type 2 diabetes (15). Studies evaluating glycemic index to guide carbohydrate recommendations have been inconsistent (16,17); however, data suggest that consumption of a diet enriched in whole grains is helpful in preventing type 2 diabetes (18). Finally, increased consumption of nuts (19) and berries (20) in the context of a diet high in vegetables and whole fruits has been correlated with reduced diabetes risk.…”
Section: Nutritionmentioning
confidence: 99%
“…Although there are some clinical data to support a modest benefit of low GI and GL diets in the management of diabetes (5,6), in the nondiabetic population the evidence is mixed (7). Meta-analysis of prospective studies supports a positive association between high GI diets and increased chronic disease risk (8), but data from randomized clinical trials indicate an inconsistent relation between dietary GI and GL values and insulin sensitivity (9), cardiovascular disease (8,10), weight loss (11,12), and cancer (13,14). Some of this discrepancy in the literature has been attributed to methodologic issues with its measurement (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%